2016
DOI: 10.1109/tevc.2015.2454857
|View full text |Cite
|
Sign up to set email alerts
|

Tunably Rugged Landscapes With Known Maximum and Minimum

Abstract: We propose NM landscapes as a new class of tunably rugged benchmark problems. NM landscapes are well defined on alphabets of any arity, including both discrete and real-valued alphabets, include epistasis in a natural and transparent manner, are proven to have known value and location of the global maximum and, with some additional constraints, are proven to also have a known global minimum. Empirical studies are used to illustrate that, when coefficients are selected from a recommended distribution, the rugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…FDC is one of the most well known predictive measures of problem difficulty for GAs 6,28,33,34 . Jones and Forrest pointed out that, the higher FDC was, the easier a fitness function for a GA would be; they also empirically determined the intervals associated with different difficulty classes of problems, and suggested that, for a binary GA, a problem was difficult when FDC fell within ( −0.15,0.15) and was easy when FDC was smaller than or equal to −0.15 33…”
Section: Other Ga‐hardness Indicators For the Test Functionsmentioning
confidence: 99%
See 1 more Smart Citation
“…FDC is one of the most well known predictive measures of problem difficulty for GAs 6,28,33,34 . Jones and Forrest pointed out that, the higher FDC was, the easier a fitness function for a GA would be; they also empirically determined the intervals associated with different difficulty classes of problems, and suggested that, for a binary GA, a problem was difficult when FDC fell within ( −0.15,0.15) and was easy when FDC was smaller than or equal to −0.15 33…”
Section: Other Ga‐hardness Indicators For the Test Functionsmentioning
confidence: 99%
“…In general, there have been two major ways to tune the epistasic degree of a test function. 1)Coordinate rotation 1,18 : A rotation of the coordinate system can change the interdependent degree between the variables; it can turn a separable function into a partially separable function, and further into a fully non‐separable function. 2)Parameter tuning: Some simulated landscapes widely used for evaluating search strategies are with tunable epistatic interactions, eg, NK landscapes 25,26 produced within the framework of Walsh polynomials, 27 and NM problems 28 proposed within the framework of general variable interaction models 29 . The epistatic degree of these landscapes can be tuned via change to a handful of model parameters. …”
Section: Introductionmentioning
confidence: 99%
“…A fitness landscape F can be defined for N variables using a general parametric interaction model of the form [2]:…”
Section: Nm-landscapementioning
confidence: 99%
“…, N }, where U k is a set of indices of the variables in the kth term, and the length |U k | is the order of the interaction. By convention [2], it is assumed that when U k = ∅, j∈U k xj ≡ 1. Also Permission to make digital or hard copies of part or all of this work for personal or classroom use is granted without fee provided that copies are not made or distributed for profit or commercial advantage and that copies bear this notice and the full citation on the first page.…”
Section: Nm-landscapementioning
confidence: 99%
See 1 more Smart Citation